2013
DOI: 10.1523/jneurosci.5651-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Selective Response Suppression Is Implemented via the Basal Ganglia

Abstract: In the welter of everyday life, people can stop particular response tendencies without affecting others. A key requirement for such selective suppression is that subjects know in advance which responses need stopping. We hypothesized that proactively setting up and implementing selective suppression relies on the basal ganglia and, specifically, regions consistent with the inhibitory indirect pathway for which there is scant functional evidence in humans. Consistent with this hypothesis, we show, first, that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
143
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(160 citation statements)
references
References 74 publications
(4 reference statements)
15
143
2
Order By: Relevance
“…This finding is consistent with functional magnetic resonance imaging studies showing a similar pattern of neural activation between the three Stop trial types (Coxon et al 2009(Coxon et al , 2012(Coxon et al , 2016. Conversely, functional imaging results from Majid et al (2013) suggest a distinct role of the selective indirect basal ganglia pathway during partial stopping. Activation of the indirect pathway should have no effect on MEP amplitude in the responding finger during Partial trials.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is consistent with functional magnetic resonance imaging studies showing a similar pattern of neural activation between the three Stop trial types (Coxon et al 2009(Coxon et al , 2012(Coxon et al , 2016. Conversely, functional imaging results from Majid et al (2013) suggest a distinct role of the selective indirect basal ganglia pathway during partial stopping. Activation of the indirect pathway should have no effect on MEP amplitude in the responding finger during Partial trials.…”
Section: Discussionsupporting
confidence: 89%
“…A likely explanation is that MEP amplitude reflects the net excitatory and inhibitory inputs whereas LICI provides a measure of inhibition only. How LICI is modulated within the proactive response inhibition network remains unclear (Majid et al 2013;Van Belle et al 2014). The present study supports the idea that proactive and reactive control mechanisms are not independent but rather reactive stopping depends on ongoing proactive control (Dunovan et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in one kind of proactive suppression paradigm, participants are cued that they might have to stop a particular muscle later in a trial. By implementing motor suppression well in advance, they are better able to stop action in a targeted way when needed (Cai et al 2011;Chikazoe et al 2009;Jahfari et al 2012;Majid et al 2013;Smittenaar et al 2013).…”
mentioning
confidence: 99%
“…More precisely, for proactive selective response suppression, new research evidence has shown that the right inferior frontal cortex seems to interact with the striatum and pallidum (8). Therefore, this basal ganglia's inhibitory indirect pathway is proposed to be activated during the present anticue task.…”
Section: Anticue Taskmentioning
confidence: 96%